2015
DOI: 10.1111/bpa.12296
|View full text |Cite
|
Sign up to set email alerts
|

Higher Prevalence of TDP‐43 Proteinopathy in Cognitively Normal Asians: A Clinicopathological Study on a Multiethnic Sample

Abstract: Transactive response DNA binding-protein 43 (TDP-43) proteinopathy is the major hallmark of frontotemporal lobar degeneration and amyotrophic lateral sclerosis. It is also present in a subset of Alzheimer’s disease cases. Recently, few reports showed TDP-43 changes in cognitively normal elderly. In Caucasians, TDP-43 proteinopathy independently correlate with cognitive decline. However, it is challenging to establish direct links between cognitive and/or neuropsychiatric symptoms and protein inclusions in neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 60 publications
2
30
0
Order By: Relevance
“…Ethnicity also impacts the prevalence of age-related diseases, such as hypertension, cardiovascular disease [65,66], and dementia [67]. Interestingly, our recently published data showed that cognitively normal Asians were more prone to exhibit TDP-43 proteinopathy, when compared to Caucasians, even after we controlled for age, sex and education [16].…”
Section: Discussionmentioning
confidence: 89%
“…Ethnicity also impacts the prevalence of age-related diseases, such as hypertension, cardiovascular disease [65,66], and dementia [67]. Interestingly, our recently published data showed that cognitively normal Asians were more prone to exhibit TDP-43 proteinopathy, when compared to Caucasians, even after we controlled for age, sex and education [16].…”
Section: Discussionmentioning
confidence: 89%
“…The Brazilian population is highly mixed genetically, mainly due to historical waves of immigration from Africa, Europe, and Asia. We have shown before that African and Japanese ancestry may modify the risk for specific neurodegenerative lesions [36,63]. Quantitative studies are necessary to investigate if the same is true for cerebrovascular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…All sections were stained with hematoxylin and eosin. Immunohistochemistry with antibodies against β-amyloid (4G8, 1:10.000; Signet Pathology Systems, Dedham, Massachusetts), phosphorylated tau (PHF-1, 1:2.000; gift from Peter Davies, New York), TDP-43 (1:500, Proteintech, Chicago, Illinois), and α-synuclein (EQV-1, 1:10.000; gift from Kenji Ueda, Tokyo, Japan) were performed in selected sections [22,36,37]. Internationally accepted neuropathological criteria were used to stage and diagnose the brain pathologies [3842].…”
Section: Methodsmentioning
confidence: 99%
“…TDP-43 pathology has been frequently shown in cognitively normal elderly individuals, and this pathology increased with age [15,3,47]. In contrast, a recent study demonstrated that advanced age at death was associated with prevalence of TDP-43 pathology in cognitively normal individuals, but not in patients with AD, DLB, or those with mixed AD and DLB [43].…”
Section: Discussionmentioning
confidence: 99%